Studi Fenomenology Pelaksanaan Handover Dengan Komunikasi SBAR - Dewi, Ratna; Rezkiki, Fitrianola; Lazdia, Wenny (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
Handover with SBAR communication is one step in achievement Patient Safety is very important implemented to reduce the incidence of accidents patient. One of Bukittinggi Hospital own patient safety program to ensure patient safety in the hospital and has been showcased in the Standard Operating Procedures (SOPs) based communications SBAR patient safety. This study aims to explore the perception of nurses in the implementation of the handover to the SBAR communication. The method used is qualitative research with phenomenological approach. Participants were a total of 11 people made up of nurses, chief nursing room and head with purposive sampling technique. Result of research showed are differences in perceptions; Socialization is optimal; Motivation in implementing the Optimally yet; The positive impact of the implementation SBAR Handover and non-performance risk SBAR handover Recommendations from this study are expected so that the structural management of the hospital can increase supervision to control the implementation of Handover with SBAR communication, and make Standard Operating Procedures for implementing Handover with SBAR CommunicationHandover dengan Komunikasi SBAR merupakan salah satu langkah dalam pencapaian Patient Safety yang sangat penting dilaksanakan untuk menurunkan insiden kecelakaan pasien. RS Kota Bukittinggi sudah memiliki program patient safety untuk menjamin keselamatan pasien di rumah sakit dan telah di tuangkan dalam Standar Prosedur Operasional (SPO) patient safety komunikasi berbasis SBAR. Penelitian ini bertujuan untuk mengekplorasi persepsi perawat dalam pelaksanaan Handover dengan komunikasi SBAR. Metode Penelitian yang digunakan ialah kualitatif dengan pendekatan fenomenologi. Partisipan berjumlah 11 orang terdiri dari perawat, kepala ruangan dan kepala bidang keperawatan dengan teknik purposive sampling. Hasil penelitian ini memunculkan lima tema yaitu Perbedaan persepsi, Sosialisasi yang optimal; Motivasi belum optimal; Adanya dampak positif pelaksanaan SBAR dan resiko tidak terlaksananya SBAR saat Handover. Rekomendasi dari penelitian ini diharapkan agar manajemen struktural rumah sakit dapat meningkatkan supervisi untuk mengontrol pelaksanaan Handover dengan komunikasi SBAR, serta membuat Standar Operasional Prosedur pelaksanaan Handover dengan Komunikasi SBAR.